The problems of selenium compound (food additive) safety - Sannotsky, Igor (MTT, 2005)
The wide use of microelement preparations for treating microelement deficiency and prophylactic use may be dangerous due to overdosage. As protective measures monitoring of the health of the population and selection of Secompounds with minimal cumulative activity are important.
Keywords: Ka